PRKAR1A mutation causing pituitary-dependent Cushing disease in a patient with Carney complex. Issue 2 (August 2017) - Kiefer, Florian W; Winhofer, Yvonne; Iacovazzo, Donato; Korbonits, Márta; Wolfsberger, Stefan; Knosp, Engelbert; Trautinger, Franz; Höftberger, Romana; Krebs, Michael; Luger, Anton; Gessl, Alois
Abstract : Context: Carney complex (CNC) is an autosomal dominant condition caused, in most cases, by an inactivating mutation of the PRKAR1A gene, which encodes for the type 1 alpha regulatory subunit of protein kinase A. CNC is characterized by the occurrence of endocrine overactivity, myxomas and typical skin manifestations. Cushing syndrome due to primary pigmented nodular adrenocortical disease (PPNAD) is the most frequent endocrine disease observed in CNC. Case description: Here, we describe the first case of a patient with CNC and adrenocorticotropic hormone (ACTH)-dependent Cushing disease due to a pituitary corticotroph adenoma. Loss-of-heterozygosity analysis of the pituitary tumour revealed loss of the wild-type copy of PRKAR1A, suggesting a role of this gene in the pituitary adenoma development. Conclusion: PRKAR1A loss-of-function mutations can rarely lead to ACTH-secreting pituitary adenomas in CNC patients. Pituitary-dependent disease should be considered in the differential diagnosis of Cushing syndrome in CNC patients.